STATE AND PROBLEMS OF TOURIST INSURANCE DEVELOPMENT IN UKRAINE - Chvertko , L. A.; Vinnytska, O. A.; Korniienko , T. O. (The actual problems of regional economy development, 2020)
The purpose of the article is to determine and generalize the existing approaches to the organization of insurance coverage against risks in the field of tourism and to substantiate the prospects for its development. In the course of the study, dialectical and abstract-logical methods, methods of the systems approach, comparison, observation, analysis, synthesis, induction, deduction, etc. The information base of the study is legislative and regulatory acts, information from the Ministry of Economic Development, Trade and Agriculture of Ukraine, the State Statistics Service of Ukraine, the National Commission for State Regulation of Financial Services Markets, scientific publications, Internet sources. The essence, types and value of insurance for providing insurance coverage for participants in the tourism market have been determined. It has been substantiated that the objective need for insurance in the field of tourism in Ukraine is due not only to the positive dynamics of the development indicators of the tourism industry, but also to the variety of types and forms of risks that accompany tourism activity, and an increase in the number of risy-creating factors. The analysis of the dynamics of indicators of medical expenses insurance, the largest segment of the travel insurance market in Ukraine, is carried out. The problems arising in the insurance of tourist risks are determined, the ways of their solution are proposed. Taking into account the importance of the tourism segment of the insurance market for the country's economy and the situation that has developed against the background of the COVID-19 pandemic, the directions for the development of travel insurance in Ukraine have been determined; the need to optimize the assortment range, improve the quality characteristics and competitiveness of existing ones, as well as develop new insurance products has been substantiated. The scientific novelty of the research lies in improving the theoretical foundations of insurance protection mechanisms for participants in tourism activities, assessing the state of insurance of risks in the domestic tourism sector and substantiating directions for increasing its effectiveness. The practical significance of the results obtained lies in the possibility of using theoretical conclusions and practical recommendations for the further development of insurance in the tourism industry. The research results can be useful for insurers and tourism industry actors to improve their performance.